ParticipACTION: Baseline assessment of the capacity available to the 'New ParticipACTION': A qualitative study of Canadian organizations - Gauvin Lise; Brawley Larry R; Chad Karen; Bauman Adrian; Faulkner Guy; McCloy Cora; Plotnikoff Ronald C; Spence John C; Tremblay Mark S (BMC, 2009)
Abstract Background Evaluation of the original ParticipACTION campaign effects focused on individual awareness, recall, and understanding. Less studied has been the impact such campaigns have had on the broader organizational capacity to mobilize and advocate for physical activity. With the relaunch of ParticipACTION, the purpose of this study was to qualitatively explore baseline organizational capacity to promote physical activity messages, programs, and services within the Canadian context. Methods Using a purposeful sampling strategy, we conducted semi-structured telephone interviews with 49 key informants representing a range of national, provincial, and local organizations with a mandate to promote physical activity. Interview data were analysed using a thematic analytic approach. Results Key informants painted a generally positive picture of current organizational capacity to promote physical activity messages, programs, and services in Canada. Will and leadership were clear strengths while infrastructure limitations remained the greatest concern. Some specific challenges included: 1) funding issues: the absence of core funding in a climate of shifting funding priorities; 2) the difficulty of working without a national physical activity policy (lack of leadership); 3) inconsistent provincial and educational sector level policies; and 4) a persistent focus on obesity rather than physical inactivity. Conclusion The data generated here can be utilized to monitor the future impact of ParticipACTION on enhancing and utilizing this organizational capacity. A range of indicators are suggested that could be used to illustrate ParticipACTION's impact on the broad field of physical activity promotion in the future.